Mechanical, absorption, and swelling properties of jute/kenaf/banana reinforced epoxy hybrid composites: Influence of various stacking sequences. Issue 11 (24th August 2022) - Thiagamani, Senthil Muthu Kumar; Pulikkalparambil, Harikrishnan; Siengchin, Suchart; Ilyas, Rushdan Ahmad; Krishnasamy, Senthilkumar; Muthukumar, Chandrasekar; Radzi, A. M.; Rangappa, Sanjay Mavinkere
Abstract: The effect of jute, kenaf, and banana fiber reinforced epoxy hybrid composites with different stacking sequences were fabricated by compression molding techniques. The pure epoxy, pure jute, pure kenaf, pure banana composites are also fabricated for comparison purposes. Tensile, flexural, inter‐laminar shear strengths, and hardness properties of the fabricated composites were investigated. Physical parameters like density, water absorption, and thickness swelling were also examined. From mechanical properties, the results are evident that when compared to hybrid composites pure banana composites have the highest tensile, flexural, interlaminar shear strength and shore D hardness value of 41, 67, 18, and 86 MPa respectively. Also, pure banana composites have better water absorption and thickness swelling percentage of 4% and 1.6%. However, KBJJBK hybrid composites exhibit a maximum tensile strength of 34 MPa, flexural strength of 54 MPa. Further BJKKJB hybrid composites possess the highest hardness value of 87, intralaminar shear strength of 17 MPa and lowest water absorption of 8% and thickness swelling percentage of 2%. Certain pure and hybrid configuration have enhanced mechanical strength, stiffness, and lower water absorption and thickness swelling properties, indicating that they are suitable for automotive structural applications.